Non-locality Of Water - Lin, Ni (fi=Lapin yliopisto|en=University of Lapland|, 2024)
Non-locality of Water aims at addressing exclusion and non-locality that happens in the water context through the combined methods of ABAR, Artistic Research and Filming. Targeting migrating pink salmon that originated in the soviet era, the result of this research process is a transnational investigation through Norway, Finland, and Taiwan that culminated into three group exhibitions.The final exhibition I am Salmon, Breathing Game, 46 W.I.P. brought together narratives from various places. These included Tenojoki in Finland, Varangerfjord in Norway, Kemijoki in Finland, and Liuqiu in Taiwan. Each narrative explored themes of exclusion beyond the local context. Together, they threaded a two-channel installation that invited viewers to consider these issues across different regions. With the aid of fieldwork and literature review, the artistic process of Non-locality of Water explores multiple layers of water—cultural, natural, colonial and underwater.